Late pleural metastasis with immunophenotypic shift seven years after resection of shoulder synovial sarcoma: a case report - Chengjin Li; Longjie Pan; Wen Min (BMC Pulmonary Medicine, 2026)
Abstract Background Synovial sarcoma is a soft tissue malignancy with a well-known propensity for late recurrence. Pleural metastasis occurring more than five years after primary resection in the absence of pulmonary involvement is exceptionally rare. Case presentation A 42-year-old man underwent local excision of a right shoulder synovial sarcoma in 2019 without adjuvant therapy or follow-up. In June 2026, he presented with right-sided chest pain and progressive dyspnea. Contrast-enhanced chest computed tomography (CT) revealed a massive right pleural effusion with diffuse pleural thickening and no pulmonary nodules; the right shoulder, partially included in the scan field, showed postoperative changes without suspicious masses. Medical thoracoscopy demonstrated pleural adhesions and scattered miliary nodules. Pleural biopsy confirmed a spindle-cell neoplasm. The primary tumour exhibited a classic immunophenotype (Vimentin⁺, Bcl-2 partial⁺, CD99 partial⁺, CK individual⁺, Ki-67 8%). In striking contrast, the pleural metastasis showed a marked immunophenotypic shift: Bcl-2, CD99, and CK turned negative, with only diffuse Vimentin and weak EMA retained, while Ki-67 rose to 50%. After excluding primary pleural spindle-cell neoplasms, a diagnosis of presumed isolated pleural metastasis from synovial sarcoma was made. The patient was started on doxorubicin plus ifosfamide and achieved symptomatic relief sufficient for hospital discharge, but a second cycle could not be administered due to poor performance status. Conclusions This case demonstrates that a dramatic immunophenotypic shift can occur during synovial sarcoma metastasis, posing a significant diagnostic pitfall. It suggests that extended pleural surveillance may be considered in long-term survivors of synovial sarcoma and highlights the importance of direct pathological comparison between primary and metastatic lesions when the immunoprofile appears atypical.